Museum - Thomas, Sophie (Romanticism on the Net, 2023)
Nominally addressed to the “museum,” this essay delineates its broad features in the Romantic period, a time of remarkable experimentation and growth, while exploring the adjacent possibilities of a digital “museum” such as RÊVE (Romantic Europe: The Virtual Exhibition). Recovering the imaginative and eclectic model of the early modern curiosity cabinet, a form of gathering and containment for the notable and the contingent that actively engages the beholder in making connections, I approach the museum less as a fixed place or structure than as a scene of action (or related actions) that bears closely on Romanticism and its materialities, particularly in the realm of memory, mobility, interiority, temporality, and presence. The museum, in this way, is what it does, or what it enables us to do, as we organize, frame, and document (as well as overlook, misappropriate, and forget) the ever-rising tide of material things that marked the turn of the nineteenth century. From paintings to travelling cases, reliquaries to trees, folding screens to books, writers’ chairs to locks of hair, RÊVE’s exhibits perform or repeat the museum’s essential gestures by assembling and mediating objects for our considered inspection, while making space for things to form associations, to re-member, to move—and in turn, to move us.